2017
DOI: 10.17802/2306-1278-2017-1-122-130
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Bare-Metal Stents for Preventing Restenosis (Part 1)

Abstract: Рестенозы металлических стентов, возникающие после имплантации, остаются нерешенной проблемой и существенно ограничивают их терапевтическую эффективность. В обзоре освещены наиболее перспектив-ные с точки зрения физиологии и клеточной биологии варианты модификации металлических поверхностей, представлены преимущества и недостатки каждого из методов. В первую часть обзора включены направ-ления, касающиеся разработки стентов с антитромботическим и антипролиферативным покрытием, так же представлены наиболее значи… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Stents [5,6] and metal plates [7,8] are the most commonly used metal implants. To investigate biocompatibility of promising metal alloys (for example, titanium nickelide), it is required to implant medical device prototypes made of the above alloys into laboratory animals, which is followed by assessment of connective tissue capsule formation, infiltration by immunocompetent cells and neovascularization [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Stents [5,6] and metal plates [7,8] are the most commonly used metal implants. To investigate biocompatibility of promising metal alloys (for example, titanium nickelide), it is required to implant medical device prototypes made of the above alloys into laboratory animals, which is followed by assessment of connective tissue capsule formation, infiltration by immunocompetent cells and neovascularization [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Audio-visual stimulation (AVS) has recently attracted increased attention due to a number of advantages: mobility, ease of implementation, fast and complex effects, capability to improve human health and functional state [ 1 – 6 ]. Recent studies have demonstrated the possibility of using AVS to improve sports training regimes [ 7 9 ] and to confirm the differential diagnosis in chronic disorder of consciousness [ 10 ]. In attempt to identify AVS mechanisms, we evaluated the efficacy of using a single AVS session to correct the functional state of the body [ 11 ], studied the effects of various AVS types [ 12 ], including music-light effects formed on the basis of human bioelectrical processes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%